Evolution of educational inequalities in life and health expectancies at 25 years in Belgium between 2001 and 2011: a census-based study - Françoise Renard; Brecht Devleesschauwer; Herman Van Oyen; Sylvie Gadeyne; Patrick Deboosere (BMC, 2019)
Abstract Background Reducing socio-economic health inequalities is a public health priority, necessitating careful monitoring that should take into account changes in the population composition. We analyzed the evolution of educational inequalities in life expectancy and disability-free life expectancy at age 25 (LE25 and DFLE25) in Belgium between 2001 and 2011. Methods The 2001 and 2011 census data were linked with the national register data for a five-year mortality follow up. Disability prevalence estimates from the health interview surveys (2001 to 2013) were used to compute DFLE according to Sullivan's method. LE25 and DFLE25 were computed by educational level (EL). Absolute differentials of LE25 and DFLE25 were calculated for each EL and for each period, as well as composite inequality indices (CII) of population-level impact of inequality. Changes over the 10-year period were then calculated for each inequality index. Results The LE25 increased in all ELs and both genders, except in the lowest EL for women. The increase was larger in the highest EL, leading in 2011 to 6.07 and 4.58 years for the low-versus-high LE25 gaps respectively in men and women, compared to 5.19 and 3.76 in 2001, namely 17 and 22% increases. The upwards shift of the EL distribution led to a limited 7% increase of the CII among men but no change in women. The substantial increase of the DFLE25 in males with high EL (+ 4.5 years) and the decrease of the DFLE25 in women with low EL, results in a substantial increase of all considered DFLE25 inequality measures in both genders. In 2011, DFLE25 gaps were respectively 10.4 and 13.5 years in males and females compared to 6.51 and 9.30 in 2001, representing increases of 61 and 44% for the gaps, and 72 and 20% for the CII. Conclusion The LE25 increased in all ELs, but at a higher pace in highly educated, leading to an increase in the LE25 gaps in both genders. After accounting for the upwards shift of the educational distribution, the population-level inequality index increased only for men. The DFLE25 increased only in highly educated men, and decreased in low educated women, leading to large increases of inequalities in both genders. A general plan to tackle health inequality should be set up, with particular efforts to improve the health of the low educated women.